2020
DOI: 10.1038/s41467-020-19309-4
|View full text |Cite
|
Sign up to set email alerts
|

Atomically dispersed Lewis acid sites boost 2-electron oxygen reduction activity of carbon-based catalysts

Abstract: Elucidating the structure-property relationship is crucial for the design of advanced electrocatalysts towards the production of hydrogen peroxide (H2O2). In this work, we theoretically and experimentally discovered that atomically dispersed Lewis acid sites (octahedral M–O species, M = aluminum (Al), gallium (Ga)) regulate the electronic structure of adjacent carbon catalyst sites. Density functional theory calculation predicts that the octahedral M–O with strong Lewis acidity regulates the electronic distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(94 citation statements)
references
References 57 publications
(45 reference statements)
2
81
1
Order By: Relevance
“…However, it has received little attention in the electrocatalytic CO 2 RR, possibly because of its insulating properties. Herein, we indeed find that loading Cu SA onto commercial Al 2 O 3 and Cr 2 O 3 Lewis acids 44 can significantly improve the activity of CO 2 methanation, and the samples with stronger Lewis acidity perform better. Moreover, when Cu SAs are supported by ultrathin, porous Al 2 O 3 , the resulting catalyst exhibits a high selectivity of 62% toward CH 4 with a corresponding current density of 153.0 mA cm −2 at −1.2 V (vs RHE).…”
mentioning
confidence: 99%
“…However, it has received little attention in the electrocatalytic CO 2 RR, possibly because of its insulating properties. Herein, we indeed find that loading Cu SA onto commercial Al 2 O 3 and Cr 2 O 3 Lewis acids 44 can significantly improve the activity of CO 2 methanation, and the samples with stronger Lewis acidity perform better. Moreover, when Cu SAs are supported by ultrathin, porous Al 2 O 3 , the resulting catalyst exhibits a high selectivity of 62% toward CH 4 with a corresponding current density of 153.0 mA cm −2 at −1.2 V (vs RHE).…”
mentioning
confidence: 99%
“…It has already been reported that Co-N-C is a good catalyst for ORR through previous DFT computational screening studies and experimental validation ( Zheng et al, 2016 ). Using O-dopant as a heteroatom has been reported for an O-C(Al) catalyst synthesized by using isomorphic metal-organic framework MIL-53(Al, Ga) ( Yang et al, 2020 ) or a multiwalled carbon nanotube catalyst ( Jiang et al, 2019 ). Moreover, the role of O-dopant heteroatoms has been elucidated in Co-NG(O) catalysts ( Jung et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a kind of valuable chemicals and potential energy carriers, H2O2 has widely been used in chemical industrial, green synthesis, environmental treatment, and fuel cell technology [16]. The annual global production of H2O2 will increase to 6 million tons by 2024 [17]. At present, most of H2O2 is synthesized at an industrial scale through a well-established anthraquinone oxidation process.…”
Section: Introductionmentioning
confidence: 99%